Steamed Sponge Bread Product Training and Expansion of the Sharia Digital Market for Housewives in Mentaos Banjarbaru: Pelatihan Produk Roti Bolu Kukus dan Perluasan Pasar Digital Syariah Pada Ibu-Ibu Rumah Tanggadi Kelurahan Mentaos Banjarbaru - Rozzana erziaty; Zakiyah Zakiyah; Abdul Wahab; Nur Arminarahmah; Yunisa Fitriana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Bolu Kukus Product Training and Sharia Digital Market Expansion for Housewives in Mentaos Village Banjarbaru is an initiative to enable non-productive group housewives to boost family income using Bolu Kukus products that are digital marketed through. exercises done in training are: 1) Production aspects, instruction in the production of various steamed Roti kukus . 2) Improvements to marketing training through online marketplaces. The method used in this community service was Participatory Rural Apracial by using the On the Job Training (OJT) model with five participants. The PPM exercise was very smoothly and according to plan, with 80% of participants rating the speakers, material demonstration, and atmosphere of PPM activities as excellent, while only 20% of participants rated the infrastructure as good